Analysis of Women’s Economic Empowerment in Sukabumi City - Iin Khairuunnisa; Endang Supriatna (Arthatama, 2018)
Facing the free market era, local governments need to make structural policiesthat support and provide incentives for the development and improvement ofSME performance. The potential of women in social life has not yet received areasonable portion. This needs to be handled wisely by the governmentconsidering women in terms of quantity ranks first in the composition of citizens.This type of research is a descriptive study with qualitative methods. Thediscussion in this article is the role of local governments to increase women’sempowerment in the economy by providing training in sewing skills, micro-creditbusiness, and women’s leadership training for women. Skills training andmicrocredit business are provided to communities where the economic level isstill below standard or underprivileged in order to improve family welfare throughthe efforts provided by the local government